Profile of Elementary School Islamic Education Teachers in Utilizing Digital Platforms for Learning in the Era of Society 5.0 - Sugiri, Wiku Aji; Wibowo, Agus Mukti; Priatmoko, Sigit; Amelia, Rizki (J-PAI: Jurnal Pendidikan Agama Islam, 2023)
There has been massive use of digital platforms in the era of Society 5.0. It has happened for at least the last ten years. Various platforms appear in various formats. However, not all of them can be used appropriately in learning. This research aims to describe the profile of elementary school Islamic education teachers in utilizing digital platforms for learning. The research subjects were elementary school Islamic education teachers in various regions. This research method is qualitative, with a descriptive approach. The data collection technique used was a survey with open questionnaires and interviews. The number of respondents in this study was 720. The results of the study show that elementary school teachers are familiar with various existing digital platforms. Instagram, WhatsApp, and YouTube are the 3 digital platforms most frequently accessed by respondents. More than 40% of respondents stated that they had installed these 3 platforms on their gadgets. Google Meet and Zoom Meeting are the platforms frequently used to facilitate online learning (52%). These conditions certainly provide opportunities related to the development of innovative and interesting learning models.